Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Kinerja Pegawai Pada Kantor Walikota Kupang - Ala, Helda Marlin; Saduk, Lispridona Magdalena (Jurnal Inovasi Kebijakan, 2025)
The purpose of this study is to analyze The Effect of The Implementation of An Accounting Information System on Employee Performance at the Kupang Mayor's Office. The independent variables studied were the Utilization of The Accounting Information System, The Quality of The Accounting Information System, and The Security of the Accounting Information System, while the dependent variable was Employee Performance. This study was conducted at Regional Work Units (SKPD) within the Kupang City Government with 30 Respondents. Data were obtained through the distribution of questionnaires completed directly by the respondents. Data analysis used the following methods: classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination using SPSS version 16 software. The results indicate that The Utilization of The Accounting Information System, The Quality of The Accounting Information System, and The Security of The Accounting Information System have a positive and significant effect on employee performance. This study is expected to serve as a reference for further research and provide recommendations for government agencies to improve employee performance through the optimal implementation of an Accounting Information System.